Pertuzumab and trastuzumab emtansine in patients with HER2-amplified metastatic colorectal cancer: the phase II HERACLES-B trial. Issue 5 (28th September 2020) - Sartore-Bianchi, Andrea; Lonardi, Sara; Martino, Cosimo; Fenocchio, Elisabetta; Tosi, Federica; Ghezzi, Silvia; Leone, Francesco; Bergamo, Francesca; Zagonel, Vittorina; Ciardiello, Fortunato; Ardizzoni, Andrea; Amatu, Alessio; et al.
Abstract : Background: HER2 is a therapeutic target for metastatic colorectal cancer (mCRC), as demonstrated in the pivotal HERACLES-A (HER2 Amplification for Colo-rectaL cancer Enhanced Stratification) trial with trastuzumab and lapatinib. The aim of HERACLES-B trial is to assess the efficacy of the combination of pertuzumab and trastuzumab-emtansine (T-DM1) in this setting. Methods: HERACLES-B was a single-arm, phase II trial, in patients with histologically confirmed RAS/BRAF wild-type and HER2+ mCRC refractory to standard treatments. HER2 positivity was assessed by immunohistochemistry and in situ hybridisation according to HERACLES criteria. Patients were treated with pertuzumab (840 mg intravenous load followed by 420 mg intravenous every 3 weeks) and T-DM1 (3.6 mg/kg every 3 weeks) until disease progression or toxicity. Primary and secondary end points were objective response rate (ORR) and progression-free survival (PFS). With a Fleming/Hern design (H0=ORR 10%; α=0.05; power=0.85), 7/30 responses were required to demonstrate an ORR ≥30% (H1). Results: Thirty-one patients, 48% with ≥4 lines of previous therapies, were treated and evaluable. ORR was 9.7% (95% CI: 0 to 28) and stable disease (SD) 67.7% (95% CI: 50 to 85). OR/SD ≥4 months was associated with higher HER2 immunohistochemistry score (3+ vs 2+) (p = 0.03). Median PFS was 4.1 months (95% CI: 3.6 to 5.9). Drug-related grade (G) 3 adverse events were observed in two patients (thrombocytopaenia); G≤2 AE in 84% of cycles (n = 296), mainly nausea and fatigue. Conclusions: HERACLES-B trial did not reach its primary end point of ORR; however, based on high disease control, PFS similar to other anti-HER2 regimens, and low toxicity, pertuzumab in combination with T-DM1 can be considered for HER2+mCRC as a potential therapeutic resource. Trial registration number: 2012-002128-33 and NCT03225937 .